2021
DOI: 10.51200/bjomsa.v5i1.2713
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost Method Of Turbidity Estimation Using A Smartphone Application In Cirebon Waters, Indonesia

Abstract: Coastal conditions are closely related to the conditions of rivers and estuaries in the region and changes in the river condition caused by human activities will affect water turbidity. Rivers discharge which carries suspended materials and pollution to the sea have an important role in affecting Cirebon Water turbidity. The aim of this study is to estimate the turbidity using a smartphone application called HydroColor. The study data are obtained in September 2020. This study used Horiba U-10 and HydroColor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The Hydrocolor (Leeuw 2014;Leeuw and Boss 2018) and EyeOnWater 26 (formerly Citclops) apps for measurement of water color, reflectance, and turbidity. Both apps have been tested for use in various water systems in several countries with mixed but promising results (Mahama 2016;Leeuw and Boss 2018;Ouma et al 2018;Yang et al 2018;Jovanovic et al 2019;Ayeni and Odume 2020;Malthus et al 2020;Al-Ghifari et al 2021;Burggraaff et al 2022). Some studies have shown that data collection should be cognisant of potentially confounding environmental variables such as cloud cover and wind speed (Ouma et al 2018).…”
Section: Examples Of Smartphone Applications For Exploration In Devel...mentioning
confidence: 99%
“…The Hydrocolor (Leeuw 2014;Leeuw and Boss 2018) and EyeOnWater 26 (formerly Citclops) apps for measurement of water color, reflectance, and turbidity. Both apps have been tested for use in various water systems in several countries with mixed but promising results (Mahama 2016;Leeuw and Boss 2018;Ouma et al 2018;Yang et al 2018;Jovanovic et al 2019;Ayeni and Odume 2020;Malthus et al 2020;Al-Ghifari et al 2021;Burggraaff et al 2022). Some studies have shown that data collection should be cognisant of potentially confounding environmental variables such as cloud cover and wind speed (Ouma et al 2018).…”
Section: Examples Of Smartphone Applications For Exploration In Devel...mentioning
confidence: 99%
“…Some use additional fore-optics to measure hyperspectrally (Burggraaff et al, 2020;Stuart et al, 2021), while most use the camera as it is Leeuw and Boss, 2018;Gao et al, 2022). Smartphone science apps are also commonly used for educational purposes and in professional research (Gallagher and Chuan, 2018;Ayeni and Odume, 2020;Al-Ghifari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%